Penyelesaian Sengketa Adat Melalui Kerta Desa Pada Masyarakat Desa Adat Di Bali Berdasarkan Asas Perdamaian - ., Karwiyah; Sonny Dewi Judiasih; Hazar Kusmayanti (Jurnal Ilmiah Penegakan Hukum, 2025)
This study aims to examine the role of customary villages in Bali in resolving customary disputes through kerta dea based on the principle of peace. The problem is focused on exploring the implementation based on the practice of village clerks in resolving disputes or customary violations that cause imbalances, so as to bring the reality that there are other dispute resolution systems in addition to formal courts. In order to approach this problem, it is necessary to study using the customary delicacies approach and dispute resolution. The data were collected through a normative juridical approach method, the research specification is descriptive analytical by describing the settlement of customary disputes through kerta desa in Balinese traditional villages based on the principle of peace associated with related regulations, legal theories, and customs. This study concludes that villages in Bali are differentiated from traditional villages and official villages. Village authorities, including customary villages, can carry out the function of dispute resolution as affirmed in the provisions of Article 103 letters (d), (e), and (f) of the Village Law. Kerta desa as the implementation of customary village authority can help as a prajuru partner institution or customary village management carry out the function of resolving customary disputes. Dispute resolution through village clerks is carried out with provisions and stages regulated in the type of pararem of Tata Titi Panepas Wicara and prioritizes peace in accordance with the principle of druwenang sareng-sareng, in Article 37 paragraph (2) of the Customary Village Regulation in Bali.